Uniform MDM2 overexpression in a panel of glioblastoma multiforme cell lines with divergent EGFR and p53 expression status - Halatsch, Marc-Eric; Schmidt, Ursula; Unterberg, Andreas; Vougioukas, Vassilios (Anticancer research, 2006)
Background: Overexpression and deletion mutation of the epidermal growth factor receptor (EGFR) gene, as well as murine double minute 2 (MDM2) overexpression have been linked to the absence of p53 gene mutations in human glioblastoma multiforme (GBM). Materials and Methods: EGFR and MDM2 messenger (m)RNA expression profiles and p53 status were examined by reverse transcription-polymerase chain rection (RT-PCR) and gene sequencing, respectively, in a set of human wild-type (wt) p53 GBM cell lines (U-87MG, U-87MG.wtEGFR and U-87MG.ΔEGFR) that exclusively differ in EGFR expression (endogenous wt EGFR expression, exogenous wt EGFR overexpression and exogenous 801-bp deletion-mutant [Δ] EGFR overexpression, respectively), as well as in two human mutant p53 GBM cell lines that differ approximately two-fold in endogenous wt EGFR mRNA expression. Results: Regardless of the underlying heterogeneity in EGFR mRNA expression and p53 status, MDM2 was similarly overexpressed among the cell lines. Conclusion: These data suggest that in human GBM (i) overexpression of wt or ΔEGFR and of MDM2 may constitute independent genetic events, (ii) overexpression of wt EGFR and mutation of p53 in GBM, although considered mutually exclusive in vivo, are not reciprocally prohibitive per se, and (iii) p53 mutations do not necessarily preclude MDM2 overexpression. In addition, this set of human GBM cell lines may constitute a suitable model for evaluating MDM2-targeted therapies in the context of various accompanying genetic alterations.